Review on The Status of Lingga Isaq Hunting Park Based on its Potentials of Flora and Fauna - Syamsul Hidayat (Media Konservasi, 1997)
Observation on the flora and fauna in Linaa lsaq Huntin, Park. with recommendations for a chan,e of status. Linaa lsaq Huntina Park (L1 HP) i.located in central Aceh, :I: SO Icm from Takenlon City. The LI Coreat hal Ionl been clauitied u a Huntinl Park but there i. Itron. IUpport for chanlinl the status to Nature Reserve or Sanctuary for several reasons. Observation on the flora and fauna were conducted from 21 May - 7 June1996 particularly in the tropical rain forest at Serule and lsaq. Data of the flora and fauna were collected throup flora inventory, quantitative vegetation analysis, and interview with local people. Population sizes of many anymals species appear to be dec:linin. and allO some oadupred species e.l. Panlhera 1tgrl8 sumalrana and Hy/oba/a spp. LI HP allO has species of plants are very important from the conservation poiat of viewin relation with the Coreat consession activities e ... Toona .JIUWtJ, Ace,. /aurlmmt, Jnlsla paI_attIctI, and DorltU pIIlche,.,.",. One alternative to conserve this foreat is to develope a butTer zone of medicinal plant estate. Plantations of species traditionally used for medicine, food, timber or otheruses could be established in collaboration with industry.